Test-retest reliability of knee extensors endurance test with elastic resistance - Lopes, Jaqueline Santos Silva [UNESP]; Micheletti, Jéssica Kirsch [UNESP]; Machado, Aryane Flauzino [UNESP]; Souto, Larissa Rodrigues [UNESP]; de Lima, Heloísa Paes [UNESP]; Vanderlei, Franciele Marques [UNESP]; Netto, Jayme [UNESP]; Pastre, Carlos Marcelo [UNESP] (Public Library of Science (PLoS), 2018)
Background Reliable clinical tests capable of measuring resistance are important tools for rehabilitation. One alternative that has recently increased in popularity is the use of elastic tubes, which stand out for being easy to handle, low cost, practical, and feasible. Objective Analyze the test-retest reliability of the knee extensors muscle fatigue resistance test (FRT) with elastic tubes. Methods A total of 116 healthy young males, aged between 18 and 30 years old, participated in the study. Participants performed three pre-test stages: orientation, load presentation, and familiarization with equipment, lasting two weeks. Subsequently, they performed the FRT on two occasions (test and retest), with an interval of seven days. The reliability analyzes were performed using the intraclass correlation coefficient (ICC) with 95% confidence interval and typical measurement error (TME), also expressed as coefficient of variation (CV%). Results The findings regarding the reliability of the test demonstrated satisfactory values (time: ICC = 0.66; 95%CI [0.50; 0.76]; CV(%) = 9.34; repetition: ICC = 0.61; 95%CI [0.46; 0.73], CV(%) = 13.66; rhythm: ICC = 0.52; 95%CI [0.35; 0.67], CV(%) = 10.29. Conclusion From the findings presented, it is concluded that the proposed clinical test with elastic tubes demonstrates evidence of acceptable values.